Anger Can Help: Clinical Representation of Three Pathways of Anger. Issue 1 (1st January 2018) - Meloy-Miller, Kierea C.; Butler, Mark H.; Seedall, Ryan B.; Spencer, Travis J.
ABSTRACT: Anger is a powerful emotion prevalent in therapy. An integrative model situating varied manifestations of anger within a purposive context of healing and repair following relationship trauma is needed. A first paper (Butler, Meloy-Miller, Seedall, & Dicus, 2017) approached anger as a psychological and relational construction of diffuse physiological arousal and provided a conceptual model of how the experience of offense interacts with a person's view of self in relation to other (VSIRO) in the formation of anger. Three resulting trajectories and pathways of anger were outlined. Here we provide clinical representations of these pathways—two pathways of hostile anger arising from pathogenic VSIROs ( inflated, with accompanying externalizing anger, and collapsed, with accompanying internalizing anger), and a third pathway of benevolent anger, arising from a balanced VSIRO. Clinical application of the model through several vignettes illuminates its use in discriminating helpful from harmful pathways of anger and developing interventions for reshaping pathogenic anger to beneficent anger.